Developmental state in chinese capitalism: formation of links between agents - Vigil Villodres, Anabel (Papeles de Europa, 2019)
The Chinese economy’s reform allowed it to shape a mode of capitalism where processes “from above”, driven by the Developmental State, and processes “from below”, based on the accumulation of local private capital, co-exist. This paper analyses the role of the DS as enabler of coordination links between agents, both public-private — through development agencies, state companies and universities —, and inter-firms, located in production clusters; deepening the internal articulation of economy and improving the position of domestic companies in the global value network as a part of a strategy to promote competitiveness at a systemic level.